Systematic Journal Review on S & OP Publications and Avenues for Future Research to Support Smart Industries - Anthony Vaz; Akalpita Tendulkar; Shaheen Mansori; Premkumar Rajagopal (International Journal of Supply Chain Management, 2019)
This research paper attempts to highlight the scarcity of articles published in the field of Sales Operations Planning (S OP) in supply chain management. Literatures in leading journals are limited in the area of S OP and there is a need to address this limitation to aid efforts to complement the demand planning process in smart industries.Â In 2010, it was recorded that only 15 papers were published and less than a handful of articles were written throughout the mid-2000s. Additionally, within these limited publications, topics have centered on structural components for operational processes rather than the demand planning or S OP process. With the advent of big data, internet of things (IOT) and Industry 4.0, there is a need for more articles to be published to support full supply chain integration.